Vernacular as lead character (Italian Review of Legal History, 2023)
The vernacular of the Florence of 1355 is the protagonist of the edition of the Florence Statutes published by Olschki in 2023 and with its vividness shines the kaleidoscopic life of the medieval city.
Keywords: Middle Ages; legal language; vernacular language; sources of law; statutory legislation